Gamma irradiation effect on fatty acid composition and conjugated linoleic acid isomers of lamb meat - Alfaia, Cristina M. M. (2008)
Comunicação Oral. Congresso Nacional. Instituto Politécnico de Beja, Escola Superior Agrária de Beja